CORRUPTION AND DECENTRALISATION: SOME EVIDENCE IN INDONESIA - Ferry Prasetyia (Journal of Indonesian Applied Economics, 2010)
This  paper  seeks  to  disentangle  the  relationship  between  decentralisation  andcorruption  In  Indonesia. The  implementations of decentralisation  in  Indonesia  in2001, on one hand give an opportunity  for  local government for more responsiveand accountable to citizens. Therefore, service delivery will improve and corruptionwill  decline. On  the  other  hand, more  decentralisation  has a  positive  impact  oncorruption, raising individual propensity to accept bribes due to an increasing anopportunities for corruption at local level. Some studies show that the implementationof decentralisation in Indonesia tends to an increasing in corruption at local level.However, some  local governments have an initiative  to addressing the problem ofcorruption through several approaches.Keywords: Decentralisation, corruption, and local government.